Screening A-site ordered quadruple perovskites for alkaline hydrogen evolution reaction via unifying electronic configuration descriptor - Sun, Ning; Li, Wenbo; Qin, Yang; Zheng, Zhichuan; Zhang, Bowen; Dong, Xiangjiang; Wei, Peng; Zhang, Yixiao; He, Xian; Xie, Xinyu; Huang, Kai; Wu, Lailei; et al. (Chinese physics B, 2024)
Dynamic adsorption processes of reaction intermediates for alkaline hydrogen evolution (HER) catalysts are still confusing to understand. Here, we report a series of A -site ordered quadruple perovskite ruthenium-based electrocatalysts A Cu 3 Ru 4 O 12 ( A = Na, Ca, Nd, and La), with the target sample SrCu 3 Ru 4 O 12 exhibiting a very low overpotential (46 mV @10 mA·cm −2 ) and excellent catalytic stability with little decays after 48-h durability test. Precise tuning A -site cations can change the average valence state of Cu and Ru, thus the plot of HER activity versus the average Ru valence number shows a volcano-type relationship. Density functional theory indicates that the Ru 4d orbitals of SrCu 3 Ru 4 O 12 possesses the most suitable d-band center position among the five samples, which might be the key parameter to determine the catalytic performance. Our work provides further insight into the discovering advanced, efficient hydrogen evolution catalysts through designing precise descriptor.